2009
DOI: 10.1186/1758-2652-12-14
|View full text |Cite
|
Sign up to set email alerts
|

Early initiation of antiretroviral therapy results in decreased morbidity and mortality among patients with TB and HIV

Abstract: IntroductionThe overlapping drug toxicity profiles, drug-drug interactions and complications of management of both HIV and tuberculosis (TB) in patients with advanced HIV have not been fully delineated.MethodsWe conducted a retrospective chart review of the outcomes of tuberculosis treatment among 69 HIV-infected patients with TB, who were hospitalized in Masih Daneshvari Hospital in Tehran, Iran between 2002 and 2006, and who received standard category 1 (CAT-1) regimens. Group I (N = 47) included those treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
25
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 14 publications
4
25
0
1
Order By: Relevance
“…ART has been available in The Gambia since 2004, so it is hard to know if there has been a reduction in TB incidence, but a recent study in Iran showed a significant reduction in TB incidence when ART was initiated for patients with CD4 counts ,100/ml (29). The World Health Organization guidelines recommend ART initiation when CD4 counts drop below 300/ml and our data suggest this is crucial in the context of retaining an adequate response to TB Ags (polyfunctional responses were lost in patients with counts below 500/ ml).…”
Section: Discussionmentioning
confidence: 99%
“…ART has been available in The Gambia since 2004, so it is hard to know if there has been a reduction in TB incidence, but a recent study in Iran showed a significant reduction in TB incidence when ART was initiated for patients with CD4 counts ,100/ml (29). The World Health Organization guidelines recommend ART initiation when CD4 counts drop below 300/ml and our data suggest this is crucial in the context of retaining an adequate response to TB Ags (polyfunctional responses were lost in patients with counts below 500/ ml).…”
Section: Discussionmentioning
confidence: 99%
“…By the end of the 50-week follow-up period, there was a 33% difference in mortality, with 59 deaths in 332 patients in the early arm and 87 deaths in 329 patients in the late arm. A retrospective review of 69 patients with HIV and TB coinfection found that an earlier initiation of ART after 2 weeks of TB treatment in patients with CD4 counts below 100 cells/l had a significant mortality reduction compared with patients with CD4 counts below 200 cells/l who started ART after 8 weeks of TB treatment (4.5% versus 27.7%, respectively; P ϭ 0.03) (243). Some experts on the U.S. guideline panel recommend an initiation of ART after 2 weeks of TB treatment for those with CD4 counts below 100 cells/l (75).…”
Section: Timing Of Initiation Of Antiretrovirals During Treatment Formentioning
confidence: 99%
“…Mortality risk is reduced by 64-95%, and excellent immunological and virological responses can be achieved, tuberculosis recurrence is reduced, and frequency of bacteriological clearance can be increased. 22,32,[105][106][107][108][109][110] Yet by the end of 2007, only 100 000 (7·3%) of an estimated 1·37 million HIV-infected tuberculosis patients worldwide were reported to have started ART. 26 Increase of uptake is a high priority and is likely to be 36 By contrast with previous guidelines, 35 WHO now recommends that all patients with tuberculosis, irrespective of CD4 cell count, should receive ART as soon as possible after start of tuberculosis treatment.…”
Section: Artmentioning
confidence: 99%